A Novel Endocrine Role for the BAT-Released Lipokine 12, 13-diHOME to Mediate Cardiac Function. Issue 2 (12th January 2021) - Pinckard, Kelsey M.; Shettigar, Vikram K.; Wright, Katherine R.; Abay, Eaman; Baer, Lisa A.; Vidal, Pablo; Dewal, Revati S.; Das, Devleena; Duarte-Sanmiguel, Silvia; Hernández-Saavedra, Diego; Arts, Peter J.; Lehnig, Adam C.; et al.
Abstract : Background: Brown adipose tissue (BAT) is an important tissue for thermogenesis, making it a potential target to decrease the risks of obesity, type 2 diabetes, and cardiovascular disease, and recent studies have also identified BAT as an endocrine organ. Although BAT has been implicated to be protective in cardiovascular disease, to this point there are no studies that identify a direct role for BAT to mediate cardiac function. Methods: To determine the role of BAT on cardiac function, we utilized a model of BAT transplantation. We then performed lipidomics and identified an increase in the lipokine 12, 13-dihydroxy-9Z-octadecenoic acid (12, 13-diHOME). We utilized a mouse model with sustained overexpression of 12, 13-diHOME and investigated the role of 12, 13-diHOME in a nitric oxide synthase type 1 deficient (NOS1 -/- ) mouse and in isolated cardiomyocytes to determine effects on function and respiration. We also investigated 12, 13-diHOME in a cohort of human patients with heart disease. Results: Here, we determined that transplantation of BAT (+BAT) improves cardiac function via the release of the lipokine 12, 13-diHOME. Sustained overexpression of 12, 13-diHOME using tissue nanotransfection negated the deleterious effects of a high-fat diet on cardiac function and remodeling, and acute injection of 12, 13-diHOME increased cardiac hemodynamics via direct effects on the cardiomyocyte. Furthermore, incubation of cardiomyocytes with 12, 13-diHOME increased mitochondrial respiration. The effects of 12, 13-diHOME were absent in NOS1 −/− mice and cardiomyocytes. We also provide the first evidence that 12, 13-diHOME is decreased in human patients with heart disease. Conclusions: Our results identify an endocrine role for BAT to enhance cardiac function that is mediated by regulation of calcium cycling via 12, 13-diHOME and NOS1. Abstract : Supplemental Digital Content is available in the text.